Validation Instrument for Measuring Teacher Attitudes and Motivation Toward Student-Centered Learning-Based Curriculum in Timor-Leste - Dos Santos, Mariano (Journal of Practice Learning and Educational Development, 2025)
This study aims to develop and validate a measurement instrument assessing teachers’ attitudes and motivation toward the implementation of a Student-Centered Learning (SCL)-based curriculum in primary schools in Timor-Leste. Employing a quantitative approach, the research involved 200 teachers from 15 schools that had adopted the SCL curriculum. Data were collected through a survey designed to evaluate teachers’ perceptions regarding the benefits of SCL, the challenges encountered, and the support received from educational institutions. An Exploratory Factor Analysis (EFA) was conducted to identify the underlying factor structure of the instrument items. This analysis helped determine the optimal number of factors and categorized the items based on distinct dimensions. Following EFA, a Confirmatory Factor Analysis (CFA) was performed to validate the alignment of the items with pre-established theoretical constructs, ensuring the instrument’s validity and reliability. The results indicate that teachers' attitudes and motivation toward SCL vary, with a majority expressing a positive outlook on the curriculum, recognizing its potential to enhance student engagement. Nevertheless, concerns remain regarding the lack of sufficient resources and professional training to effectively implement SCL strategies. These findings highlight the critical role of positive teacher attitudes and strong motivation in the successful implementation of SCL, where teachers serve as key facilitators in the learning process. By producing a valid and reliable instrument, this research provides valuable empirical data on the factors influencing SCL implementation in Timor-Leste. The outcomes are expected to inform policymakers and contribute to improving education quality through more targeted and supportive measures for teachers in developing country contexts.